1961
DOI: 10.1136/bmj.1.5239.1557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medical and Surgical Vagotomy on the Augmented Histamine Test in Man

Abstract: When the evolution of surgery in the treatment of duodenal ulcer is traced it is evident that during the last half-century surgeons have directed their efforts along two main channels. Firstly, search has been made for an operation which would cure the existing ulcer and guarantee prevention of recurrent ulceration; new procedures have been numerous and varied, but, after a brief vogue, most have been shown deficient in some respect. Secondly, and more recently, there have been well-planned clinical trials wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1962
1962
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 3 publications
1
31
0
Order By: Relevance
“…In the hope of finding a method for forecasting the result of vagotomy, hundreds of clinical tests have been made to study the blocking action of combinations of hexamethonium and atropine (McArthur et al 1960, Gillespie & Kay 1961, Johnston et al 1966. The theoretical basis of such tests has never been investigated.…”
Section: Discussionmentioning
confidence: 98%
“…In the hope of finding a method for forecasting the result of vagotomy, hundreds of clinical tests have been made to study the blocking action of combinations of hexamethonium and atropine (McArthur et al 1960, Gillespie & Kay 1961, Johnston et al 1966. The theoretical basis of such tests has never been investigated.…”
Section: Discussionmentioning
confidence: 98%
“…There was no definite evidence of inhibition of responses during the pre-operative 'insulin secretion tests' in patients with high total gastrin-like activity in their antra, as was observed in dogs with Heidenhain pouches responding to large doses of injected gastrin extracts (Gillespie and Grossman, 1963). The possible role of gastrin in the aetiology of duodenal ulceration has been suggested by Gillespie and Kay (1961) who showed that antrectomy alone led to healing of the duodenal ulcer in four patients. The Zollinger-Ellison syndrome provides an extreme example of possible effects of excessive gastrin (or gastrin-like substance) in circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Reserpine at 1 mg/kg/time was intraperitoneally administered every other day, totally 5 times [10] and the animal was challenged with the antigen on the day 5 after the last administration. Hexamethonium at 50 mg/kg [11] was intraperitoneally administered 30 min and 6-OH-DA at 100 mg/kg [12] was intravenously administered 2 days before the antigen challenge.…”
Section: Drug Treatmentmentioning
confidence: 99%